Effect of relativistic plasma on extreme-ultraviolet harmonic emission from intense laser-matter interactions - Krushelnick, K; Rozmus, W; Wagner, U; Beg, F; Bochkarev, S; Clark, E; Dangor, A; Evans, R; Gopal, A; Habara, H; Mangles, S; Norreys, P; et al. (2008)
Experiments were performed in which intense laser pulses (up to 9×1019 W/cm2) were used to irradiate very thin (submicron) mass-limited aluminum foil targets. Such interactions generated high-order harmonic radiation (greater than the 25th order) which was detected at the rear of the target and which was significantly broadened, modulated, and depolarized because of passage through the dense relativistic plasma. The spectral modifications are shown to be due to the laser absorption into hot electrons and the subsequent sharply increasing relativistic electron component within the dense plasma. © 2008 The American Physical Society.